Improving Students Activity and Students Learning Outcomes by Using Cooperative Learning with Snowball Throwing type - Sholahudin Al Ayubi (Universitas Islam Jember, 2020)
The purpose of the research to know the using of cooperative learning model with Snowball Throwing type can increase the students’ activities and to know the using of cooperative learning model with Snowball Throwing type can increase the students’ learning outcomes. The kind of the research is PTK with qualitative approach. The subjects of the research are students of class XI at As-Salafi Balung. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative. The results of the research there is increased activity and student learning outcomes.Keywords: snowball throwing, students activity, and learning outcome